Alterations of regional cerebral glucose metabolism using 18F-fluorodeoxyglucose positron-emission tomography/computed tomography and electroencephalography analysis during mindfulness breathing in Anapanasati meditation: A preliminary analysis - Chotipanich, Chanisa; Tepmongkol, Supatporn; Wongsawat, Yodchanan; Jantarato, Attapon (World Journal of Nuclear Medicine, 2021)
Anapanasati is a core meditation of a breath-centered practice in the Buddhist Theravada tradition, which may have some neurological mechanism effects on the brain. To gain insight into the neurological mechanisms involved in Anapanasati meditation, we measured the alterations of regional cerebral glucose metabolism during Anapanasati meditation using positron-emission tomography/computed tomography (PET/CT) and electroencephalography (EEG) analysis. This prospective study was conducted in six right-handed volunteer participants (two men, four women; aged: 32–67 years) who underwent 18F-fluorodeoxyglucose (18F-FDG) PET/CT scans to compare the alterations of regional cerebral glucose metabolism during normal consciousness and Anapanasati meditation states. Spectral EEG analysis was performed throughout the investigations. Statistical parametric mapping was used for the 18F-FDG PET/CT image analyses. The visual analysis demonstrated moderate-to-marked increased metabolism in posterior cingulate cortex in all six patients, while mild-to-moderate increased uptake in the whole frontal lobe was also observed in four patients and precuneus in four patients. Meanwhile, the semiquantitative analysis yielded an increase of regional cerebral glucose metabolism in the right mid-to-posterior cingulate gyrus (P < 0.000), with visible alpha waves on the frontal of the EEG findings. Our semiquantitative analysis showed a significantly increased metabolism only in the posterior cingulate cortex, but visually, there was also an increased metabolism in the whole frontal lobe in most of the patients correlating with EEG findings.
Keywords: Anapanasati meditation; cerebral metabolic rate of glucose; electroencephalography; positron-emission tomography